Synthetic Aperture Radar for Through-Wall Detection and Imaging of Complex Vibrating Targets - Corbett, Brandon; Andre, Daniel; Muff, Darren; Morrow, Ivor L.; Finnis, Mark V. (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.Low frequency Synthetic Aperture Radar (SAR) is a proven solution for generating through-wall images, although obtaining a clear picture of the structure and contents of buildings has proven to be difficult. Whilst the effects created by moving objects within a SAR image have been investigated before, the complex effects moving objects have upon a SAR image when located behind a wall, are less known. This is especially the case when the motion of the object being imaged is of vibration and when multipath effects influence the artefacts produced within the SAR image. This occurs when the transmitted SAR microwaves reflect from other objects within the imaged scene, before being detected by the receive antenna. The research presented, investigates these complex SAR phenomena with multistatic radar geometries, using the Cranfield University Antennas and Ground Based SAR (AGBSAR) laboratory. This research is conducted in support of the Dstl Remote Intelligence of Building Interiors (RIBI) programme, and addresses the problem of the detection of running machinery within buildings, amongst other challenging scenarios.
Keywords: 'Through wall SAR'; 'Vibrating target'; 'SAR Imaging'; 'DSDS17'; 'DSDS17 poster'; 'Photogrammetry and Remote Sensing'; 'Antennas and Propagation'